Analisis Semantik atas Kata “Thayyibah” dalam al-Qur’an - Nur Shadiq Sandimula (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Semantic Analysis of the word "Thayyibah" in the Qur'anSemantic analysis is a classical approach to comprehending the meaning of Qur'anic text utilized by Islamic scholars (ulama) in the form of tafsir since Islam's rise centuries ago. This semantic analysis can be utilized to analyze the ethical-religious terms in the Qur'an, which is the word thayyibah. This research aims to reveal the semantical meaning of the word thayyibah in the Qur'an. This research employs the content analysis method and uses a semantic analysis approach related to the study of weltanschauunglehre. This research begins by defining the meaning of semantics and then analyzing the semantical meanings of the word thayyibah with its derivatives. Furthermore, explaining the definitions in several Qur'anic verses. The explanation is based on the elaboration of the Qur'an interpreters (mufassirs). They revealed its subtle meanings and semantical correlations. The result shows that the word thayyibah in the Qur'an has Islamic religious meaning. Usage of the term kalimah thayyibah, interpreted as the word of Unity (Tawhid), gains a central position in the reality of human life. This concept spawns an ethical-religious worldview that perceives religion as the basis for perceiving every human life phenomenon. At the level of individual life, thayyibah means living a good life. In the marital domain, thayyibah means choosing a suitable life partner and giving birth to good offspring. From the social aspect, thayyibah is in the form of good social dealings. Moreover, at the national level, thayyibah creates a safe and secure national state. The word thayyibah undergoes semantical changes within its semantic field, from its original meaning that connotes something good in worldly affairs to something that is much broader, including tauhid and here-after meanings. The Qur'an has reformed the word conceptual structure, its semantic field, vocabulary, and its basic vocabulary. That preceded projects a jahili weltanschauung to the Islamic weltanschauung